Clinical profile of Dengue patients in a rural tertiary care centre of coastal Kerala - Poornima, H.; John, Juby (International Journal of Research in Medical Sciences, 2018)
Background: Dengue epidemic is a major health problem in India. According to the directorate of National Vector Borne Disease Control Programme (NVBDCP) over 18,700 cases of dengue have been reported in India in 2017.Kerala has reported the highest number of dengue related deaths in the country. The aim of the present study is to find out the clinical profile of patients admitted with dengue fever during the epidemic in 2017 in a rural tertiary care centre in coastal Kerala. Methods: 341 patients who were admitted in the medicine department of a rural tertiary care centre in Kerala with Dengue were included in the study. W.H.O case definitions were used for the diagnosis. Complete blood counts, RBS, serum creatinine and liver function tests and E.C.G were carried out in all patients. Chest X ray, Echocardiogram, ultrasonogram, MRI and CSF study were done when indicated. Results: Males predominated. 317 were diagnosed as dengue fever, 12 as dengue hemorrhagic fever and 12 had dengue shock syndrome. Only four patients succumbed to death. Aminotransferases were elevated in 74.4%. In all cases AST was more than ALT. Head ache and myalgia were the common symptoms at the time of presentation. 72 patients had abnormal ECG, but all had normal ECG at the time of discharge, indicating a transient change during the episode. Conclusions: Careful monitoring of clinical and biochemical parameters is necessary during dengue epidemics. Atypical manifestations of dengue should also be considered in the differential diagnosis of various diseases in different organ systems.